1985
DOI: 10.3109/02844318509074516
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Some Psychological Aspects of Subcutaneous Mastectomy

Abstract: The report describes how the patients reacted to the information given them before the operation, their reactions following the operation, and their sexual behaviour before and after the operation. Patients who have undergone subcutaneous mastectomy with simultaneous insertion of implants have to cope with two different psychological factors: loss of the breast and sudden acquisition of an unfamiliar substitute. This study indicates that these factors may interfere with each other in a detrimental way. It may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Another study reported that 5% had later regrets about the surgery (Borgen et al, 1998). The psychological and sexual problems in women with prophylactic mastectomy may approximate those seen in women with oncological mastectomy (Gyllenskold et al, 1985, Meyer et al, 1986. However, the psychological effects of bilateral mastectomy have not been determined for large groups of asymptomatic women undergoing this procedure to prevent breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported that 5% had later regrets about the surgery (Borgen et al, 1998). The psychological and sexual problems in women with prophylactic mastectomy may approximate those seen in women with oncological mastectomy (Gyllenskold et al, 1985, Meyer et al, 1986. However, the psychological effects of bilateral mastectomy have not been determined for large groups of asymptomatic women undergoing this procedure to prevent breast cancer.…”
Section: Introductionmentioning
confidence: 99%